Media, Ritual, dan Solidaritas: Meninjau Kembali Teori Durkheim melalui Peringatan Haul Guru Sekumpul - Bambang Dwi Waluyo; Achmad Bayu Chandrabuwono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Haul Guru Sekumpul is one of the biggest religious traditions in Indonesia that brings together millions of participants from various regions to commemorate KH. Muhammad Zaini Abdul Ghani, better known as Guru Sekumpul. This activity not only serves as a religious commemoration, but also reflects the value of togetherness, solidarity, and deep spirituality. This research aims to reinforce the argument that in fact the feedback process between group involvement and emotional reactions strengthens solidarity, both in mechanical and organic contexts, thus creating deeper social bonds. Thus, mechanical and organic solidarity are not separate but interrelated. Through a qualitative approach, this research analyzes how mechanical and organic solidarity interact with each other in the context of this activity. The results show that mechanical solidarity, characterized by shared values and beliefs, serves as the foundation for a more complex organic solidarity, where individuals with different roles depend on each other. The findings also serve as a critique of Émile Durkheim's theory of solidarity. In addition, the use of social media and traditional media plays an important role in disseminating information and organizing activities, creating a sense of community among congregants. This is also a new additional factor that is in line with the changing times but was previously undeveloped during Émile Durkheim's time. Thus, Haul Guru Sekumpul is not only a religious event, but also a symbol of collective power that binds people in a common goal, creating a harmonious and respectful community.